Investigation and analysis of aging behavior and tensile fracture study on precipitation hardened al7075-white cast iron particulate reinforced composites. Issue 1 (1st January 2021) - B M, Gurumurthy; Hindi, Jamaluddin; Kini U, Achutha; Sharma, Sathya Shankara
Abstract: In this research work the machining waste white cast iron powder (WCI) is introduced in the age hardenable Al7075 alloy matrix with the objective of enhancing the tensile properties by well-known age hardening treatment. This material holds good in light duty dies where in the strength-related characteristics improvement is the order of the day. In view of this the effect of aging kinetics on the hardness pattern and tensile strength of stir cast Al7075-white cast iron (WCI) particulate reinforced composites in as cast and peak aging conditions is investigated. The composite is cast by two step liquid stir casting route. During precipitation hardening heat treatment, reinforcement weight percentage (internal variable) and aging temperature (external variable) are considered to be the major strengthening variables. To understand the nature of failure in tensile study, fracture surface analysis is carried out using SEM. The experimental values revealed that there is a substantial enhancement in the desired properties during the precipitation hardening treatment, if the strengthening variables are properly controlled. Hardness and tensile strength of the composite have increased with increase in weight percentage of reinforcement and reduction in aging temperature. Maximum hardness and tensile strength are observed when Al7075 alloy is reinforced with 6 weight% of WCI, aged at 100ᴼC. SEM images of tensile fracture surface exhibits abundant cup-like depressions or dimples as well as river patterns indicating mixed mode of failure. The equally aligned facets (dendrites) present in the peak-aged fracture surfaces is the evidence for the attainment of optimum (peak) aging condition. The aim of the present research work is to improve the hardness-related properties by the combined effect of precipitation of secondary phases (intermetallics) through aging treatment and dispersion strengthening by the introduction of hard reinforcement WCI.